Study on the Innovation Process in Precision Agriculture using patent mapping using NPK sensors in the production of fertilizers - Reis, Marcello; Reis, Patricia; Martinez, Maria Elisa; Lopes, Youlia; Guimarães, Glendo; de Oliveira, Alexandre Maniçoba (Journal of Mechatronics Engineering, 2021)
With the constant population growth, Agroindustry has sought to innovate in its products and processes, with innovation and precision agriculture in the use of NPK fertilizers, and the determination of the concentrations of NPK present in the soil, makes it necessary for the correction of such levels in order to obtain greater soil efficiency and crop productivity, this adopted practice requires the use of sensors both in the bio manager and in the soil for the result to be really valid. There is a need to evaluate the scenario in which the NPK sensors developed to date are inserted in order to contribute to the knowledge in this area of study. One of the ways to carry out such an evaluation is through the information contained in the patent documents, the objective of this article. With the search for these documents, 95 patent documents were selected after reading and analyzing the abstracts, where the presence in both the soil and the soil and in the bio manager, we had 66% of the cases, and China (96%), which is the country that consumes the most fertilizers, as parents that most protects its innovations with emphasis on the Jiangsu region.